Democracies Adrift: How the European Crises Affect East-Central Europe. Issue 5 (1st November 2016) - Brusis, Martin
Abstract : Electoral landslides, corruption scandals, mass protests, a declining satisfaction with democracy and weakened democratic accountability in Hungary and Poland pose questions about where East-Central European democracies are heading and how their paths are related to the crisis of European integration. I argue that the crises of economic and European integration have discredited the nexus between economic integration and prosperity and made responsive and responsible government more incongruent. Multi-dimensional policy spaces facilitated the growth of anti-establishment parties in the Czech Republic and Slovenia. Higher performance expectations of citizens, the mixed electoral system, and missing institutional safeguards of societal-political pluralism rendered Hungary's democracy more vulnerable.